Exploring paruresis (‘shy bladder syndrome’) and factors that may contribute to it: a cross-sectional UK survey study - Hayley Anne Hutchings; Abi Kehinde (BMJ Open, 2024)
Objectives To assess the prevalence and severity of paruresis (‘shy bladder syndrome’) in a population of university staff and students and to determine if there was any relationship between demographics, self-esteem, presence of social anxiety disorders and negative toilet experiences and paruresis.Design We undertook an anonymised cross-sectional online survey using Microsoft Forms. We invited participants aged 18 and over to complete the survey which included demographic information; any pre-existing medically or self-diagnosed anxiety-related conditions; Shy Bladder Scale (SBS); Rosenberg Self-Esteem Scale (RSES) and questions about using school toilets in their younger life. We defined ‘mild’ and ‘severe’ paruresis based on total SBS cut-off scores of greater than or equal to 31 and greater than or equal to 40. We calculated prevalence of paruresis, and explored differences in self-esteem, school toilet experience and social anxiety disorders between individuals with and without paruresis. Multivariable logistic regression was used to determine which variables had any influence on having a ‘mild’ and ‘severe’ paruresis diagnosis.Setting We distributed the survey to all staff and students via their university email address as well as promoting the survey on university social media sites.Results We received responses from 356 individuals. Most participants (237, 66.6%) were within the 18–30 year age category and most (277, 77.8%) were white. There were 221 (62.1%) females, 119 (33.4%) males and 16 (4.5%) other genders. The prevalence of ‘mild’ paruresis was 25.8% and of ‘severe’ paruresis 14.9% in this sample. 73.0% indicated that they had at least one medically or self-diagnosed anxiety disorder. There was a statistically significant difference in the total SBS score between individuals with and without an existing anxiety disorder (8 vs 19, <0.001). The adjusted odds of ‘mild’ paruresis were higher for men than women (OR 3.39; 95% CI 1.90 to 6.06), lower for those with a lower RSES score (OR 0.90; 95% CI 0.85 to 0.96), lower for those for a lower school toilet experience score (OR 0.88; 95% CI 0.78 to 0.99) and higher for those with at least one anxiety disorder (OR 3.164; 95% CI 1.52 to 6.59). The adjusted odds of ‘severe’ paruresis were higher for men than women (OR 2.60; 95% CI 1.32 to 5.12), lower for those with a lower RSES score (OR 0.90; CI 0.84 to 0.97) and higher for those with at least one anxiety disorder (OR 2.99 (1.18–7.56)).Conclusion Large organisations should consider measures to help manage anxiety and improve toilet experiences. These could include resources and signposting to manage anxiety disorders and single-occupancy toilets and toilets in quiet areas to limit anxiety associated with shy bladder syndrome.